The role of violence in the classics of Brazilian Social Thought - Bruno de Souza Lessa; Jaqueline Silinske (Ciências Sociais Unisinos)
This essay had the objective of problematizing the role of violence in Brazilian social life and of discussing the relevance it poses in three classics of Brazilian Social Thought. By analyzing how the issue was treated in Casa-Grande & Senzala, Raízes do Brasil, and Formação do Brasil Contemporâneo, we aimed at defending the argument that, although the emergence of violence appears to be, to certain common sense, a new phenomenon, its widespread employment has been an integrative element of social interactions in Brazil, but is mainly used against more vulnerable segments of society. Furthermore, by taking advantage of each author’s conceptual apparatuses, we introduced a discussion not only about the role of violence in the Brazilian colonial era, but also about its continuity over time and the social-historical manifestations it has in contemporaneity. We concluded that these seminal books give support to our argument insofar as violence appears in all of them as an element that grants cohesion to society as it ensures the submission of the dominated to the dominant.